The history writer’s tale : historical fiction and the depiction of identity in Michiel Heyns’s ‘the typewriter’s tale’ and ‘bodies politic’ - Medalie, David (University of Pretoria, 2023)
Thesis (DLitt (Creative Writing))--University of Pretoria, 2022.